Towards a contextual understanding of human rights. Issue 4 (29th November 2019) - Moka-Mubelo, S.J., Willy
ABSTRACT: Should human rights be understood within a specific context? In order words, should the discourse on human rights be historically contingent? If so, isn't there a risk that they will lose their universal character? I argue that the standard of human rights provided by major documents and treaties of human rights must be respected, but at the same time, there are rights that must be developed in accordance with a particular context and specific needs of the people. Some might object that in contextualizing human rights they run the risk of losing their universal character. The argument of the universal character of human rights does not always meet a unanimous consent of everyone. Some non-Westerners thinkers, for example, reject the idea of the universality of human rights because, they argue, human rights reflect and perpetrate the western culture, which is sometimes at odd with non-western cultures. They then advocate a reconstruction and clarification of the moral, political, and legal status of human rights. This requirement of clarifying the different aspects of human rights status appears in Ingram's argument when he affirms that the theoretical clarification of the apparent incoherence of the Universal Declaration of Human Rights, regarding the moral, political, and legal status of human rights must be sensitive to the multiple functions and justificatory grounds of human rights. Thus, the leading question to be answered in this paper will be: should there be a definitive list of rights for all contexts and all circumstances?